Bioactivities of Compounds from Elephantopus scaber, an Ethnomedicinal Plant from Southwest China - Wang, Jianjun (Hindawi Publishing Corporation, 2014)
Elephantopus scaber is an ethnomedicinal plant used by the Zhuang people in Southwest China to treat headaches, colds, diarrhea, hepatitis, and bronchitis. A new δ-truxinate derivative, ethyl, methyl 3,4,3′,4′-tetrahydroxy-δ-truxinate (1), was isolated from the ethyl acetate extract of the entire plant, along with 4 known compounds. The antioxidant activity of these 5 compounds was determined by ABTS radical scavenging assay. Compound 1 was also tested for its cytotoxicity effect against HepG2 by MTT assay (IC(50) = 60 μM), and its potential anti-inflammatory, antibiotic, and antitumor bioactivities were predicted using target fishing method software.